The moderating role of fintech app usage in lower-income households in Malaysia: a financial well-being roadmap - Sabri, Mohamad Fazli; Magli, Amirah Shazana; Nazuri, Nur Shuhamin; Ahmad Suhaimi, Siti Shazwani; Othman, Mohd Amim; Burhan @ Jaohari, Nik Ahmad Sufian (International Academy of Financial Consumers, 2023)
In Malaysia, the B40 group represents households with a monthly income below MYR4,850 (USD1,093), constituting the lowest 40% of earners facing economic challenges. Amid rising living costs and employment instability, managing finances becomes crucial. Fintech apps, known for accessibility and convenience, offer various financial services. A cluster sampling strategy was used to identify 1,948 B40 households from across Peninsular and East Malaysia to serve as the study's sample population. The data was obtained through a cross-sectional study then scrutinised via SEM-PLS. This study aims to determine factors such as locus of control, financial knowledge, and financial behaviour concerning the usage of fintech apps that impact the financial well-being of Malaysian B40 households. The study findings indicate a significant positive correlation between an individual's Financial Knowledge and Locus of Control toward Malaysia B40 Financial Well-Being. The study suggests that Financial Behaviour partially mediates the relationship between Financial Knowledge, Locus of Control, and Financial WellBeing. The study also indicates that Fintech App Use moderates the relationship between Financial Knowledge, Locus of Control, and Financial Well-Being. The present study contributes to the theoretical understanding of financial well-being by investigating the mediating and moderating factors influencing this construct.